Technical evaluation for hydrogen storage for vehicles - Eldemerdash, Usama (2010)
Today the world faces the problem of dependency on fossil fuels, which are rapidly decreasing. With the decline of global fossil fuel reserve and the increasing demand for energy, there is a sincere need to develop alternative fuels for automobiles. Hydrogen is a environmentally friendly and renewable energy source. It has been considered an ideal fuel for replacing fossil fuels. Currently, Liquid hydrogen (LH2) system (with a density of 51 kg/m3 and 14 wt %) is close to practical use. However, the cost of using LH2 as a transportation fuel is nearly twice that of gaseous hydrogen (GH2), due to the liquefaction process, increased fuel transportation costs and more complex manipulation of the fuel. If the intention is to use hydrogen on a large scale, storage is a key problem. Storage research is focused on the following technologies compressed gas, cryogenic hydrogen, and metal hydrides, but the number of alternative methods is growing, including carbon novel materials, chemical hydrides, and glass microspheres are also being considered. This paper reviews the different solutions for hydrogen storage and highlights the promising technology for vehicle use